2014
DOI: 10.1186/1472-6963-14-437
|View full text |Cite
|
Sign up to set email alerts
|

Explaining variation in Down’s syndrome screening uptake: comparing the Netherlands with England and Denmark using documentary analysis and expert stakeholder interviews

Abstract: BackgroundThe offer of prenatal Down’s syndrome screening is part of routine antenatal care in most of Europe; however screening uptake varies significantly across countries. Although a decision to accept or reject screening is a personal choice, it is unlikely that the widely differing uptake rates across countries can be explained by variation in individual values alone.The aim of this study was to compare Down’s syndrome screening policies and programmes in the Netherlands, where uptake is relatively low (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 29 publications
3
89
0
1
Order By: Relevance
“…The proportion declining cFTS is low compared to other European countries [2] . A Dutch study on the impact of macrolevel demographic, social and health care and delivery factors on the uptake of cFTS identified a charging fee for above-standard health care and an emphasis on 'right not to know' as being factors leading to a reduced uptake.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The proportion declining cFTS is low compared to other European countries [2] . A Dutch study on the impact of macrolevel demographic, social and health care and delivery factors on the uptake of cFTS identified a charging fee for above-standard health care and an emphasis on 'right not to know' as being factors leading to a reduced uptake.…”
Section: Discussionmentioning
confidence: 72%
“…A Dutch study on the impact of macrolevel demographic, social and health care and delivery factors on the uptake of cFTS identified a charging fee for above-standard health care and an emphasis on 'right not to know' as being factors leading to a reduced uptake. The social context and positive framing of the offer at the service level could play a role in the high uptake in Denmark [2] . However, a risk assessment for T21 should only be obtained after making an informed decision, and thus, a part of the population is expected to decline screening for T21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed a decrease in children born with Down’s syndrome of 28%–50% in the Netherlands and 18%–59% in Western Australia 25 44. Those who fear an increase of the abortion rate refer to the high number of abortions in, for example, Denmark, but due to cultural differences between countries it might be hasty to conclude that in the Netherlands the uptake and abortion rate will increase to the same extent 45. This remains to be seen in practice.…”
Section: Analysis Of Three Leading Routinisation Argumentsmentioning
confidence: 99%
“…More nuanced differences in DSS programmes and policies may also impact on preferences. Crombag et al 35 compared DSS programmes in Denmark, the Netherlands, and UK and speculated that variation in DSS uptake rates between these countries are influenced by how the offer of DSS is framed and viewed. For example, in Denmark (highest uptake) DSS is free and is offered in a social context where screening is viewed by many women as a routine part of prenatal care.…”
Section: Direct Choice Between Nipt Invasive Testing or No Testmentioning
confidence: 99%